Self-Determination as a Psychological and Positive Youth Development Construct - Eadaoin K. P. Hui; Sandra K. M. Tsang (The Scientific World Journal)
This paper presents a review of self-determination as a positive youth development construct. The definition and conceptualization of the concept are examined from the perspective of self-determination theory and the functional theory of self-determination. Theories of self-determination from the perspective of motivation and skills enhancement are examined. Factors contributing to self-determination, such as autonomy-supportive teaching and parenting style, culture, efficacy of intervention programmes, and the educational benefits of self-determination for students, are discussed. Strategies to promote self-determination in an educational context and implications for further research and practice are discussed.